Mechanical properties of masonry brick using pineapple fibre - Mohammed Alias Yusof,; Muhammad Azani Yahya,; Viknesvaran Munikanan,; Zubaidah Rosli, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sustainable development in the construction sector should be a participant in utilising the waste materials for the betterment of the industry. Turning waste materials into some application can contribute to the attainment and greening of the planet. In addition, research needs to be carried out to encourage the waste materials into useful building materials and economic. An idea of practicing environmental awareness should be adopted as opposed to simply considering the rapid development as the whole project objective. Inclusion of natural fibres in bricks has been proved to enhance strength development. This study investigates the pineapple fibres inclusion on the mechanical properties of masonry bricks. Experiments were conducted on masonry bricks with pineapple fibre percentage of 0, 0.25%, 0.50% and 0.75% to determine the compressive strength and water absorption of the bricks according to ASTM C67-17 Standard (2017). It was found that by incorporating an 0.5% of pineapple fibres into masonry bricks, the strength properties of the bricks were significantly improved. As a result, this research paper recommends using 0.5% of pineapple fibre as an optimal fibre content in masonry bricks reinforced with pineapple leaf fibre in the application in construction industry.